DataCite - Contributing to PIDs Infrastructure in Africa - Obileye, Olatunbosun (My University, 2023)
The presentation was made during AfricArxiv webinar series. The presentation focused on the facts about PIDs landscape in Africa, identifying the key factors that is impeding the institutionalization of open science in the region while providing the various initiatives from DataCite to address the challenge in the region. Details about DataCite's engagement in the region involving various stakeholders were identified while services that brings metrics and visibility to research outputs were highlighted in the presentation.
Keywords: Persistent Identifiers; Repositories; Infrastructure